Gender-responsive social protection for gender equality and climate resilience - Roy, Shalini (CGIAR GENDER Impact Platform, 2023)
Shalini Roy's presentation on the PROTECT work package highlights that stakeholders increasingly seek guidance on designing social protection to promote gender equality and women's climate resilience. She cites an ethnographic study from Bangladesh that suggests gender-responsive social protection, paired with livelihood and disaster resistance training, promoted short-term coping during climate events and women's longer-term adaptation and climate resilience. The fireside conversation with Raashee Abhilashi, national coordinator for IIED's 'Enhancing climate resilience impacts of India's social protection' programme emphasized the necessity of gender-sensitive social protection programs.